Inverse kinematics of a serial-parallel robot used in hot forging process - My, Chu Anh (Vietnam Journal of Mechanics, 2016)
In hot extrusion forging process, the use of robot arm for transferring heavy billets can reduce downtime, improve productivity, reduce worker fatigue and optimize the use of energy and manpower. To increase the stiffness of the robot and force the end-effector move in directions parallel with the ground surface, two parallel links are added to a standard serial manipulator. This modification of the structure could make it a bit of challenge in the system modelling and controlling. This paper addresses the inverse kinematics analysis that is the central issue for developing autonomous control modes of the robot application.